اختيارات الإمام ابن حبيب المالكي من خلال كتاب النوادر و الزيادات لابن أبي زيد القيرواني - كتاب الجمعة أنموذجا - - سليمان كرم; المختار سواحلة (جامعة محمّد بوضياف المسيلة, 2025)
يُعنى هذا البحث ببيان اختيارات ابن حبيب المالكي التي نقلها ابن أبي زيد القيرواني في كتابه النوادر و الزيادات - كتاب صلاة الجمعة أنموذجا-، حيث تكلمنا عن حياة ابن حبيب الشخصية و العلمية وعصره من جوانب شتى، كما تم استقراء جميع اختيارات ابن حبيب في باب الجمعة، حيث كان البحث منصبا على المسائل التي خالف فيها ابن حبيب مشهور المذهب أو عامة المالكية... وقد خلصنا إلى أنّ ابن حبيب كان مؤثرا في واقعه، مصلحا في مجالات الحياة بقلمه ولسانه، تجلى ذلك في تآليفه وفتاويه الكثيرة، كما اتضح لنا شديد عنايته بآراء الإمام مالك، لكنه كان متحررا يقول بما يوافق الحق و الدليل ولو خالف المذهب. This research examines the choices of Ibn Habib al-Maliki, as reported by Ibn Abi Zayd al-Qayrawani in his book, "Al-Nawadir wa al-Ziyadat" (The Rarities and Additions), a model of which is the book "The Friday Prayers." We discuss Ibn Habib's personal and scholarly life and his era from various perspectives. We also examine all of Ibn Habib's choices in the chapter on Friday prayers, focusing on issues in which he differed from the well-known Maliki school of thought or the general Maliki school of thought. We conclude that Ibn Habib was influential in his own life, a reformer in all areas of life with his pen and tongue. This is evident in his numerous writings and fatwas. We also find his deep concern for the views of Imam Malik. However, he was a liberal, speaking in accordance with truth and evidence, even if it contradicted the school of thought